Самоорганизация versus государственный патернализм: сравнительный анализ установок жителей Львова и Донецка (1994–2004) - Сусак, В. (Социология: теория, методы, маркетинг, 2007)
The author of the article analyses how economic and religious-cultural predictors as well as factors of regionalism and age differentiation influence on the attitudes of population from Lviv and Donetsk in comparative range "Self-organization versus StatePaternalism" during 1994-2004. In general, the research shows that respondents at all levels of analysis and in all contexts were to a certain extent disposed to state paternalism in contrast to self-organization. The most influential predictor noticeably determining the character of change in respondents' attitudes was an economic factor. Then follow religious-cultural, regional, and age differentiation factors.